ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATERI HIMPUNAN PADA SISWA KELAS VII SMP SWASTA AL-WASHLIYAH 8 MEDAN TAHUN AJARAN 2017/2018 - Anggini Hasanah; Fibri Rakhmawati (State Islamic University of North Sumatra, 2018)
This research is aimed to know: (1) The kind of error students doinsloving The Material of Reading Exercise of Himpunan based onNewman Procedure in class VII of SMP Swasta Al-Washliyah 8Medan, (2) The causes of the students error insolving The Materialof Reading Exercise of Himpunan based on Newman Procedure inclass VII of SMP Swasta Al-Washliyah 8 Medan.This research isqualitative research. The subject of the research is the students ofseven grade SMP Swasta Al-Washliyah 8 Medan Academic Year2017/2018. The choice of this research subject is by taken 6 of 34for students of VII-1 class, each consist of 2 higher level group, 2medium level group, and 2 lower level group. This grouping isbased on the ranks of the student. Then, are chosen 2 studentswiththe lowest correct answer on each group. Data collection procedureon this research use the method of the test and interviewing. Everysubject research was interviewed of their work result on Materialof Reading Exercises of Himpunan. Data analysis of this researchuse Miles and Huberman Model consist of data reduction, datapresentation, and conclusion. The validity test of the data in thisstudy was carried out by Triangulation Technique.The resultsshowed that students made mistake in the type of ComprehensionError, Transformation Error, and Process Skill Error. This error canbe seen from the following percentage: Comprehension Erroroccurs as much as 14,71%, Transformation Error occurs as muchas 43,38% (this error is the most mistakes made by students), andProcess Skill occurs as much as 1,47%. The cause of the error isnot being able to change it into the symbol of Himpunan. They arenot used to write the questions, unable to plan a solution for theproblem, wrong in determining the right formula for the questiongiven, not realize their mistakes in the count of operationsperformed, and can not count operations correctly.